Experimental study on the behaviour of reinforced concrete deep beams with large circular openings strengthened using CFRP - Chong, Wen Khai (2015)
This experimental research was conducted to study the behaviour of unstrengthen RC deep beams with openings and strengthened using Carbon Fiber Reinforced Polymer (CFRP). Strengthening configuration of CFRP-wrap used in this study were U-wrap and surface-wrap which applied with one layer of CFRP and in vertical alignment (90o). Four RC deep beams which included a solid control beam, a beam with two large circular openings, beams with two large circular openings strengthened using U-wrap and surfacewrap were tested to failure under four-point loading. All the beam specimens were in a dimension of 120 x 600 mm and 2400 mm in length. The support and loading point were located at 300 mm and 800 mm from the edge of the RC deep beams, respectively. Circular openings was designed with a standard of 0.45h which considered as large circular openings in a diameter of 270 mm that located 435 mm from the edge of the RC deep beams. Shear span-to-depth ratio (a/h) in this study was 0.83 in which the distance between the loading point and the support was 500 mm in order for the beam specimens to fail in shear region. RC deep beam with large circular openings, NS-BCO greatly reduced the beam strength, approximately 51.20 % as compared to the control beam. On the other hand, RC deep beam with circular openings strengthened using U-wrap, UWBCO increases the beam strength up to almost 85.0 % as compared to NS-BCO. Hence, the most effective strengthening method was U-wrap, UW-BCO which re-gained the beam strength up to 90.28 % as compared to control beam.